SENTIMENT ANALYSIS OF SERVANT LEADERSHIP IN SMP IT INSAN MANDIRI - Totong Suparman; Dana Budiman; Nur Hasan Kurniawan (RADJA PUBLIKA, 2025)
This study aims to analyze sentiments toward servant leadership practices at SMP IT Insan Mandiri Sukabumi. Servant leadership emphasizes the values ​​of devotion, empathy, and empowerment toward organizational members, in this case teachers, staff, students, and parents. This study uses a qualitative approach with methods. The method used is sentiment analysis based on text mining with Orange software on qualitative data in the form of open responses, comments, and testimonies, and testimonies, collected through interviews. The results of the analysis indicate that the majority of teachers have positive sentiments toward the implementation of servant leadership by the principal who is considered supportive, open, and builds a collaborative work atmosphere. However, there are also a small number of neutral and negative sentiments related to the lack of consistency in the implementation of servant leadership values ​​at the operational level. This study recommends strengthening internal communication, continuous leadership training, and participatory evaluation as strategies to improve leadership quality. These findings are expected to be an important contribution in developing a more humanistic educational leadership model that is responsive to the needs of the school community.